Behind the Seal: Determinants of Going Concern Audit Opinions - Hayuningtyas, Talisa; Amirya, Mirna (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
A going concern audit opinion serves as an important indicator for stakeholders in evaluating a corporate entity's potential to continue its operations, particularly during periods of economic uncertainty. In Indonesia, incidents of financial distress and the risk of delisting among infrastructure companies underscore the importance of understanding the factors that shape auditors’ going concern assessments. This study examines the effect of financial distress, opinion shopping, audit tenure, institutional ownership, audit committee, and independent commissioners under the Agency Theory framework. The sample consists of 48 infrastructure companies listed on the Indonesia Stock Exchange from 2020 to 2022, selected through purposive sampling, resulting in 144 firm-year observations. Logistic regression analysis reveals that financial distress reduces the probability of obtaining a going concern audit opinion, while having an active audit committee increases it. Opinion shopping, audit tenure, institutional ownership, and independent commissioners show no significant relationship. These findings indicate that financial conditions and the effectiveness of audit committee oversight play a key role in shaping audit opinions. Consequently, companies should mitigate financial risks, reinforce governance practices, and support regulations that limit audit engagement periods to safeguard auditor independence.